Strategi Komunikasi Kader TBC Komunitas dalam Mendorong Terduga TBC Memeriksakan Diri ke Fasilitas Layanan Kesehatan - Hermansyah, Wawan (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the communication strategies used by community TB cadres to encourage TB suspects to go to health services. The research method used was qualitative with a case study approach in several areas with high TB ​​prevalence. Data was collected through in-depth interviews with TBC cadres, direct observation of communication activities, and analysis of related documents. The research results showed that TB cadres used four strategies, namely a personal and empathetic approach, fact-based education, and conveying testimonials from TB survivors. Apart from that, cadres also collaborate with community leaders to increase the effectiveness of health messages. This research provides valuable insights for designing more effective health communication programs in TB control.